Biophilic Boost: Enhancing Productivity and Satisfaction at Work - Zufra Ashraf; Deepti Pande Rana; Syed Mohammad Amin Naqvi (International Journal of Architectural Design and Planning, 2024)
In an era where workplace well-being and productivity are increasingly recognized as critical to organizational success, the concept of biophilic design has gained significant attention. Biophilic Boost: Enhancing Productivity and Satisfaction at Work" explores the integration of natural elements into office environments to improve employee well-being, satisfaction, and productivity. This study delves into the psychological and physiological benefits of biophilic design, including reduced stress, increased creativity, and enhanced focus. The research highlights case studies and empirical evidence that support the positive impact of biophilic design on employee performance and job satisfaction. Through an analysis of case studies and empirical research, the paper provides compelling evidence that biophilic design not only elevates job satisfaction but also contributes to a more sustainable and health-conscious work environment. Ultimately, this study advocates for the broader adoption of biophilic principles in workplace design, emphasizing their role in creating sustainable, healthy, and productive work environments.
Keywords: Biophilic Design; Natural Elements; Work environment; employee engagement; employee satisfaction; sustainable design; workplace productivity